Mengenal Keberagaman Budaya, Kekayaan Budaya Indonesia, Dan Mengenal Nusantara Melalui Program Kampus Merdeka Pertukaran Mahasiswa Merdeka Batch 2 (PMM 2) - Wulan Sundari Siboro; Indah Tiur Marintan Hutabarat (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The Merdeka Student Exchange is a program from the merdeka or independent learning campus where students from one university can exchange to another university for one full semester. The increased sense of nationalism and love for the country after participating in the independent student exchange program is very important for every Indonesian citizen, especially for the younger generation who are the nation's successors. This independent student exchange program teaches good communication, high nationalism, community service, and exploring the archipelago. All of these things are covered in the Nusantara Module program.